Biochemical parameters of osteogenesis in epiphysis of mice irradiated and repopulated with syngeneic bone marrow - Włodarski, K H; Reddi, A H (Folia biologica, 1989)
Whole-body irradiation of BALB/cann mice with 600 R of gamma rays produces a profound atrophy of the spleen and diminishes alkaline phosphatase activity in the homogenates of epiphysis. The acid phosphatase activity remains unchanged until day 10, then slightly declines. Incorporation of 45Ca into epiphysis is practically not impaired following irradiation. Repopulation of irradiated animals with 1-1.5 million nucleated syngeneic bone marrow cells restores spleen weight within 6 days, but until day 11 the activity of alkaline phosphatase of epiphysis remains lower. Full recovery of enzyme activities was not observed until day 14, but on day 28 these activities returned to the normal level. Histological inspection did not reveal a full recovery of bone marrow in the epiphysis of irradiated animals until day 14, possibly because of trapping of the vast majority of stem cells by the spleen and liver. On day 28, however, epiphyses were completely filled with the bone marrow.
Keywords: Mice, Inbred BALB C; Transplantation, Isogeneic; Mice; Epiphyses; Bone Marrow; myši inbrední BALB C; kostní dřeň; Bone Marrow Cells; alkalická fosfatasa; vztah dávky záření a odpovědi; transplantace kostní dřeně; myši; Female; epifýzy; buňky kostní dřeně; Alkaline Phosphatase; kyselá fosfatasa; Calcium; Osteogenesis; vápník; ženské pohlaví; zvířata; Bone Marrow Transplantation; transplantace izogenní; osteogeneze; Animals; Dose-Response Relationship, Radiation; Acid Phosphatase